Analisis Aksebilitas Pengguna Difabel Pada Eksisting di Neha HUB, Cilandak Jakarta - Elsa Fasfahisofkha; Sri Riswanti; Rio Setia Monata (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study discusses the accessibility of persons with disabilities in the Neha Hub public space in Cilandak, South Jakarta. Although regulations regarding the rights of persons with disabilities have been established through Law Number 8 of 2016, their implementation in public facilities is still not optimal. This study uses a qualitative descriptive method through field observations, interviews with managers, and literature studies to identify existing conditions and compare them with accessibility standards. The results show that various facilities at Neha Hub, such as the entrance area, parking lot, toilets, creative space, and prayer room, do not meet universal design standards that are friendly to persons with disabilities. The obstacles encountered include narrow circulation spaces, the use of inappropriate flooring materials, the absence of ramps, tactile paving, informative signage, and special toilet facilities for persons with disabilities. These findings confirm that there is still a gap between regulations and implementation in the field. The conclusion of this study emphasizes the need to redesign public facilities and infrastructure to be more inclusive through the application of universal design so that public spaces can be accessed fairly and comfortably by all levels of society, including people with disabilities.